Randomized controlled clinical trial on the antiseptic efficacy of polihexanide 0.04% on acute traumatic wounds. Issue 4 (April 2018) - Payne, B.; Simmen, H.-P.; Csuka, E.; Hintzpeter, M.; Pahl, S.; Brill, F.H.H.
Summary: Prevention of wound infections is a challenge in clinical practice. The aim of this study was to assess the efficacy of polyhexamethylene biguanide (PHMB, polihexanide) 0.04% on acute traumatic wounds. It was a randomized, double-blind, placebo-controlled prospective trial which included 61 patients. The polihexanide group showed a significant decrease in log10 colony-forming units (cfu) ( P < 0.001) after 60 min treatment in comparison to baseline cfu, whereas the Ringer solution group did not show a significant change in cfu during 60 min treatment. Treatment of polihexanide 0.04% resulted in a significant reduction of bacterial load in acute traumatic wounds.